Family Caregiver’s Psychosocial Characterization of the Patient with Oncological Conditions - Juan Luis Figueredo Tornés; Anierka Lanz Rodés; Marely Figueredo Fonseca; Magaly Hidalgo Rodríguez; Maricel Figueredo Fonseca; Laritza Benítez Téllez (Revista Finlay, 2023)
Background: among the problems faced by family caregivers of patients with oncological diseases is the fact that they take care of their relatives without the specific knowledge or skills required for the exercise of care, which generates an overload in them. Objective: to identify the main psychosocial characteristics of the family caregiver of the patient with oncological conditions in the urban area of Niquero, during the period from November 2019 to March 2022. Methods: a descriptive study was carried out in the period from November 2019 to March 2022 in the Niquero municipality in the Granma province. The universe of study was made up of 305 family caregivers of patients with oncological conditions, choosing a sample of 255 of them by means of the established criteria. The variables analyzed were: age, sex, level of education, psychosocial factors present. An intentional and probabilistic sampling was carried out. Results: the age group prevailed in the family caregivers of cancer patients aged 50-59 years, the female sex and as level of education, the basic secondary predominated, fear was the emotional state most referred to by them. In the social background, the unfavorable economic situation was the one that prevailed, as well as the level of inadequate family coping with the role of caregiver. Conclusion: fear, the unfavorable economic situation and the inadequate level of coping with the role of caregiver, were the main psychosocial characteristics that prevailed.